Intuitive eating has reduced the chances of being overweight in university students during the COVID-19 pandemic - Souto, Caroline Rodrigues; Salaroli, Luciane Bresciani; da Silva, Gabriela Grillo; Cattafesta, Monica; Silva, Yasmin Franco Rodrigues; Soares, Fabíola Lacerda Pires (Frontiers in Nutrition, 2024)
Introduction University students have been particularly affected during the COVID-19 pandemic, and several sociodemographic and behavioral factors may be associated with the risk of overweight in this population. The aim of this study was to assess the impact of the pandemic on the eating behavior and nutritional status of university students, and the factors associated with these changes, especially the role of intuitive eating in this process. Methods This is a repeated measures observational study with data collected in the first and third year of the COVID-19 pandemic in Brazil, from students over the age of 18 in the undergraduate programs of a federal university in southeastern Brazil. The survey was conducted using an online form. Eating behavior was assessed using the “Intuitive Eating Scale–2”. Results 251 university students took part, most of them female with a median age of 22. There was an increase in body mass index (BMI) and intuitive eating score between the two periods. In the first year of the pandemic, being female and using tobacco reduced the chances of students being overweight. Living in a marital relationship, worrying about weight gain and body dissatisfaction increased the chances of this outcome. In the third year of the pandemic, it was observed that practicing restrictive diets, having inadequate body perception, worrying about weight gain and living in a marital relationship increased the chances of students being overweight. Being female and eating more intuitively, in line with bodily needs, reduced these odds, demonstrating a protective role in this scenario. Conclusion There was an increase in BMI and intuitive eating score during the pandemic. Sociodemographic, lifestyle and behavioral variables had both a positive and negative influence on nutritional status. Intuitive eating was shown to be a protective factor during this period, reducing the chances of being overweight in this population. Thus, more intuitive eating may favor greater weight stability, and may, therefore, have helped to reduce the impact of the pandemic on weight gain. In this way, people who ate more intuitively partially resisted the context that favored weight gain (stress, changes in diet and physical inactivity).